(untitled) (SCIENCE TIME JOURNAL, 2026)
This article examines the development of digital citizenship skills through the teaching of discourse analysis in language education. In the context of rapid digital transformation, modern education systems are increasingly expected to equip learners and teachers with competencies that extend beyond linguistic knowledge to include responsible, ethical, and critical participation in digital environments. The study explores the theoretical foundations of digital citizenship and its integration into language teaching practices, with particular attention to discourse analysis as a pedagogical tool. It discusses how analyzing authentic digital texts can foster critical thinking, media literacy, and awareness of online ethical standards among language learners and pre-service teachers. The article also highlights the pedagogical significance of incorporating discourse analysis activities in developing students’ ability to evaluate, interpret, and produce meaningful communication in digital spaces. The findings suggest that discourse analysis serves as an effective instructional approach for enhancing digital citizenship skills and should be systematically integrated into contemporary language teaching methodologies.